THE DISCREPANCY BETWEEN ENGLISH TEACHERS’ PERCEPTION AND IMPLEMENTATION TOWARD THE TEACHING CREATIVITY - Permadi, Gede Agus; Padmadewi, Ni Nyoman; Artini, Luh Putu (Universitas Pendidikan Ganesha, 2020)
This study was carried out to explore the teachers’ perception toward their creativity in teaching, to observe their creativity in teaching, and to describe the discrepancy between the teachers’ perception and the observed implementation. The study used embedded mixed method as the research design where the qualitative data were dominant and used as the primary data, while the quantitative data were used as the supportive data. SMK Negeri 1 Bangli was chosen as the research setting. Two English teachers were selected as the research subjects. There were two questionnaires which were used to collect the data: the self-rated questionnaire and classroom observation sheet. Then, the data were respectively analyzed, quantitatively and qualitatively. The interview was conducted to elaborate the result of the analyzed data. The results reveal that 1) the teachers perceive themselves as creative in implementing their creativity in teaching; 2) the teachers are observed as slightly creative in implementing the creativity in the actual teaching process 3) there is a discrepancy between the teachers’ perception and the implementation toward their creativity in teaching.